DIGITAL LITERACY MAPPING FOR HOUSEWIFE IN ENTREPRENEURSHIP - Diah Sri Rejeki (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The increase in household needs which is marked by the increase in the prices of necessities that must be met by a household is the main trigger for women as housewives to work to meet their household needs. One of them is by doing entrepreneurship. Today’s entrepreneurial housewives use digital media more for marketing because it helps them inform and interact directly with consumers. This study aims to map the digital literacy of entrepreneurial housewives in Karawang Regency. The research method used was a survey and used a questionnaire as a means of collecting data. Mapping is divided into 3 levels, namely digital competence, digital use and digital transformation. The level of digital literacy of housewives in entrepreneurship is high at the digital competence level, where housewives have realized the importance of using digital media as a reliable promotional tool. Meanwhile, at the digital usage and digital transformation level, it is quite high where housewives have the ability to manage digital media in business activities and innovate to provide convenience to a wide audience.